The Effectiveness of E-Government in The Service of Identity Cards (KTP) at the Palopo City Population and Civil Registration Service - Aslinda, Andi; Makmur, Farhan; Rukmana, Novayanti Sopia (Universitas Negeri Makassar, 2023)
Digital government or what is known as Electronic Government (e-Gov) has developed with the presence of Information and Communication Technology (ICT). This research aims to find out how effective E-Government is in the Population Identification Card (KTP) service at the Palopo City Population and Civil Registration Service. This research uses a qualitative approach. The data collection procedures used are observation, interviews and documentation. Checking the validity of the data using Triangulation. The results of this research show that effectivenessE-Government The Population Identification Card (KTP) service at the Palopo City Population and Civil Registration Service is running less effectively. This research uses elements of success based on the results of studies and researchHarvard JFK School of Government which consists of three indicators, namelySupport, Capacity andValue. Based on these three indicators, indicatorsCapacity in the poor category refers to the capacity or ability of the Palopo City Population and Civil Registration Service in the form of finance, information technology and human resources who have expertise in the IT field which is inadequate in KTP services.